2014
DOI: 10.4103/2152-7806.139610
|View full text |Cite
|
Sign up to set email alerts
|

Totally extradural spinal en plaque meningiomas - Diagnostic dilemmas and treatment strategies

Abstract: Background:Meningiomas are the second most common intraspinal tumors, constituting ~25% of all intraspinal tumors; however, in the context of extradural spinal lesions, the diagnosis of meningioma is an uncommon one. Purely extradural spinal meningiomas, especially of the en plaque variety, frequently mimic metastatic disease and may result in inadequate therapy.Case Description:We report two cases of totally extradural en-plaque meningiomas of the spine, one each in the cervical and dorsal spine. We present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The presence of a "sole" extradural spine meningioma is entirely rare [2]. Common tumours located in the spinal extradural space are metastatic spinal tumour and lymphoma, hence the dilemma in preoperative diagnosis which was also emphasis by Saryedekar et al in the two cases reported by them [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of a "sole" extradural spine meningioma is entirely rare [2]. Common tumours located in the spinal extradural space are metastatic spinal tumour and lymphoma, hence the dilemma in preoperative diagnosis which was also emphasis by Saryedekar et al in the two cases reported by them [7].…”
Section: Discussionmentioning
confidence: 99%
“…An entirely spinal extradural meningioma especially of the 'en plaque; variety poses a dilemma in pre-operative diagnosis [2,7]. In this index case, a pre-operative diagnosis of C4-T1 schwannoma of the spine in view of its location and C7 nerve root attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, intraoperative pathological examination using either frozen section examination or squash cytology is very important. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%